Structured Mentoring Strategies: Its Correlation to the Clinical, Leadership and Research Skills of Novice Nurses - Gallego, Randy Ian (JPAIR Multidisciplinary Research, 2018)
Mentoring activities in the clinical area by nurse supervisors are helping the entry-level nurses to the social milieu of the hospital to ensure that competencies are set, so that safe and competent patient care is delivered. Hence, this study examined the senior staff nurses’ mentoring activities and their relationship to the nursing skill development as perceived by the novice nurses in Lanao del Norte, Philippines. The study used descriptive-inferential research design involving 71 novice-nurse respondents. The data obtained were analyzed using the Pearson correlation. The findings revealed that while in general, mentoring activities given by the senior nurses indicate an increased competence in the nursing skills of the novice nurses as safe practitioners; it also showed partial impact regarding the competencies on leadership and research. The mentoring activities on conducting scientific inquiry further revealed a significant correlation with the nursing proficiency of the respondents as competent practitioners, managers, and researchers. Therefore, the study concludes that activities geared towards coaching and mentoring neophyte nurses in the clinical areas have a beneficial influence on the development of their needed core competencies in nursing practice. Formally structured preceptorship programs should be adapted to help novice nurses become more apposite, responsive and streamlined care practitioners.
Keywords: Nursing; mentoring activities; nursing skill development; descriptive-inferential design; Lanao del Norte; Philippines